From Local Wisdom To Global Harmony - Faizal, Ahmad; Wijayanti, Cici; Sholihah, Dawimatus; Ramadhani, Kurniawan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Indonesia, as the country with the world’s largest muslim population and rich local wisdom, faces serious challenges in achieving sustainable economic development. Inequalities in wealth distribution, the exploitation of natural resources, and the dominance of a capitalist economic system often neglect the values of justice and sustainability. On the other hand, local traditions such as ”sasi” in Maluku, ”subak” in Bali, and ”gotong royong” in various regions reflect economic ethics that align with principles, including distributive justice (al-‘adl), sustainability (istidam), and the entrusted stewardship of the earth (khalifah fil ardh). This article aims to analyze the potensial integration of islamic economic values with Indonesia’s local wisdom as a model of sutainable development oriented toward global harmony. Using a qualitative approach based on literature review and contextual analysis, this study finds that the synergy between Islamic economics and local wisdom can provide alternative solutations to issues of socio-economic inequality, environmental degradation, and identity crises in the era of globalization.the findings of this study imply the strengthening of a velue-based economic paradigm that is not onlyrelevant at the local level but also capable of contributing to a more just, ethical, and harmonious global economic order.